Facile synthesis of an antimony-doped Cu/Cu2O catalyst with robust CO production in a broad range of potentials for CO2 electrochemical reduction. Issue 40 (11th October 2021) - Chen, Hongyu; Wang, Zhaojie; Cao, Shoufu; Liu, Siyuan; Lin, Xiaojing; Zhang, Yi; Shang, Yizhu; Zhu, Qiuying; Zhou, Sainan; Wei, Shuxian; Wei, Baojun; Sun, Daofeng; et al.
Abstract : The pre-adsorbed *CO is the key for high selectivity of CO2 RR to CO on Cu/Cu2 O–Sb. Abstract : The electrocatalytic CO2 reduction reaction (CO2 RR) on copper-based catalysts is a promising method to produce valuable chemicals, but its selectivity is much lower than expected largely due to insufficient research on the structure of new materials. Herein, the antimony-doped Cu/Cu2 O (Cu/Cu2 O–Sb) catalyst is developed for a highly selective CO2 RR to CO. The synthesized Cu/Cu2 O–Sb exhibits intensive suppression of hydrogen evolution, a low overpotential and high faradaic efficiency (FE) towards CO. The CO selectivity is as high as ∼95% with a partial current density of ∼6.3 mA cm −2 at −0.9 V and maintains over 90% in a broad range of potentials. DFT calculations reveal that the doping of antimony achieves the distinct activation of CO2 and suppression of hydrogen evolution. Meanwhile, the pre-adsorbed *CO significantly promotes the desorption of the neighboring *CO, which is the key for high selectivity of CO2 RR to CO. This work will provide a new consideration for the origin of high selectivity during the CO2 RR and pave the way toward design of highly selective CO2 reduction catalysts.